The Hugo Boss Prize 2010. - Guggenheim Museum, New York (New York : The Solomon R. Guggenheim Foundation, 2010)
Fei, Cao; Feldmann, Hans-Peter; Ondák, Roman; Raad, Walid; Haghighian, Natascha Sadr; Weerasethakul, Apichatpong
Published following the selection of the finalists for the Hugo Boss Prize 2010
boek
Keywords: Art, Modern -- 21st century; Hugo Boss Prize